Evaluation on the quality of Malaysian refined palm stearin - Ahmad Bustamam Farah Khuwailah; Yeoh Chee Beng; Sulaiman Najwa; Saw Mei Huey (Oilseeds and fats, crops and lipids, 2022)
The quality of Malaysian palm stearin was monitored through a twelve-month survey in 2018, by participation of palm oil refineries and oleochemical plants from Peninsular Malaysia and Sarawak. Quality parameters requirement as listed in the Palm Oil Refinery Association of Malaysia (PORAM) specification such as moisture, impurities, free fatty acids, slip melting point, peroxide value and iodine value were determined. Other identity characteristics analyses as detailed in the palm stearin specification namely Malaysian Standard MS 815:2007 and Codex Alimentarius CXS 210-1999 documents were also analyzed, which were apparent density, refractive index, fatty acids composition, triacylglycerols, etc. Results obtained from this survey indicated that the quality of Malaysian palm stearin complied with the requirements specified in MS 815:2007 and Codex CXS 210-1999 documents. The iodine value determined was ranged from 28 g I2/100 g oil to 48 g I2/100 g oil, with 60.9% of the palm stearin tested were in the range of 30 g I2/100 g oil to 35 g I2/100 g oil. Meanwhile, some deviations are found in the average of parameter such as refractive index, apparent density, slip melting point, oleic and palmitic acids of the palm stearin produced. These deviations could be due to the improvement in current fractionation technologies causing less olein entrainment in stearin products, which resulted of harder stearin fraction in the sample itself, giving a more representative reading of the parameters.